In silico analysis of Mn transporters (NRAMP1) in various plant species - ÖZYİĞİT, İBRAHİM İLKER (SPRINGER, 2016)
Manganese (Mn) is an essential micronutrient in plant life cycle. It may be involved in photosynthesis, carbohydrate and lipid biosynthesis, and oxidative stress protection. Mn deficiency inhibits the plant growth and development, and causes the various plant symptoms such as interveinal chlorosis and tissue necrosis. Despite its importance in plant life cycle, we still have limited knowledge about Mn transporters in many plant species. Therefore, this study aimed to identify and characterize high affinity Arabidopsis Mn root transporter NRAMP1 orthologs in 17 different plant species. Various in silico methods and digital gene expression data were used in identification and characterization of NRAMP1 homologs; physico-chemical properties of sequences were calculated, putative transmembrane domains (TMDs) and conserved motif signatures were determined, phylogenetic tree was constructed, 3D models and interactome map were generated, and gene expression data was analyzed. 49 NRAMP1 homologs were identified from proteome datasets of 17 plant species using AtNRAMP1 as query. Identified sequences were characterized with a NRAMP domain structure, 10-12 putative TMDs with cytosolic N- and C-terminuses, and 10-14 exons encoding a protein of 500-588 amino acids and 53.8-64.3 kDa molecular weight with basic characteristics. Consensus transport residues, GQSSTITGTYAGQY(/F) V(/I) MQGFLD(/E/N) between TMD-8 and 9 were identified in all sequences but putative N-linked glycosylation sites were not highly conserved. In phylogeny, NRAMP1 sequences demonstrated divergence in lower and higher plants as well as in monocots and dicots. Despite divergence of lower plant Physcomitrella patens in phylogeny, it showed similarity in superposed 3D models. Phylogenetic distribution of AtNRAMP1 and 6 homologs inferred a functional relationship to NRAMP6 sequences in Mn transport, while distribution of OsN-RAMP1 and 5 homologs implicated an involvement of NRAMP1 sequences in Mn transport or a cross-talk between in Fe-Mn homeostasis. Interactome analysis further confirmed this cross-talk between Mn and Fe pathways. Gene expression profile of AtNRAMP1 under Fe-, K-, P-and S-deficiencies, and cold, drought, heat and salt stresses revealed various proteins involving in transcription regulation, cofactor biosynthesis, diverse developmental roles, carbohydrate metabolism, oxidation-reduction reactions, cellular signaling and protein degradation pathways. Mn deficiency or toxicity could cause serious adverse effects in plants as well as in humans. To reduce these adversities mainly rely on understanding the molecular mechanisms underlying Mn uptake from the soil. However, we still have limited knowledge regarding the structural and functional roles of Mn transporters in many plant species. Therefore, identification and characterization of Mn root uptake transporter, NRAMP1 orthologs in various plant species will provide valuable theoretical knowledge to better understand Mn transporters as well as it may become an insight for future studies aiming to develop genetically engineered and biofortified plants.
Keywords: Transporter family; Motif signature; Interaction partner; Homology search; Conserved motif; 3D modelling; GENE FAMILY; IRON UPTAKE; DIFFERENTIAL REGULATION; STRUCTURE PREDICTION; MANGANESE UPTAKE; PHOTOSYSTEM-II; ROOT HAIRS; ARABIDOPSIS; MEMBERS; EVOLUTIONARY